2012
DOI: 10.3382/ps.2011-02076
|View full text |Cite
|
Sign up to set email alerts
|

The identification of c-Kit-positive cells in the intestine of chicken

Abstract: The ultrastructure of the interstitial cells of Cajal (ICC) has been examined in birds, but the distribution of these cells remains obscure because a suitable marker is lacking. In the present study, the identification and expression of c-Kit-positive cells in the chicken intestine were demonstrated by means of in situ hybridization histochemistry and the expression of the c-Kit gene by real-time quantitative PCR. Two types of cells stained positive for c-Kit mRNA. The first group consisted of spindle-shaped o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 36 publications
4
12
0
Order By: Relevance
“…Furness (2006) and Lomax et al (2006) reported the ganglionar organization of myenteric neurons on the digestive tube wall in different species of mammals. Yang et al (2012) observed the ganglionic and isolated cell distribution in the ileum of 65 days old broilers. This corroborates with the results observed in this study.…”
Section: Nadphdmentioning
confidence: 98%
See 3 more Smart Citations
“…Furness (2006) and Lomax et al (2006) reported the ganglionar organization of myenteric neurons on the digestive tube wall in different species of mammals. Yang et al (2012) observed the ganglionic and isolated cell distribution in the ileum of 65 days old broilers. This corroborates with the results observed in this study.…”
Section: Nadphdmentioning
confidence: 98%
“…Yang et al (2012), studying the nitrergic neuron density in the ileum of broilers of 65 days old, found an average of 30.59 neurons per mm 2 in their ileum, while the current study found 24.38 neurons per mm 2 in group C. The number of neurons was described by different researchers from different mammal species in different intestinal segments, and, according to the authors, this fact is associated with the higher functional activity in each segment under study (Miranda-Neto et al, 2001;Furness, 2006). The myenteric plexus responds to different types of stimuli and conditions, whether deleterious or not, changing their chemical characteristics or their functional structure to keep the digestive system homeostasis (Lomax et al, 2006).…”
Section: Nadphdmentioning
confidence: 99%
See 2 more Smart Citations
“…Isg15 is robustly induced by different stimuli, including type 1 IFNs, lipopolysaccharide, viruses, and oncogenes [3-6]. Similar to ubiquitin conjugation, ISGylation of target proteins occurs in a three-step cascade mechanism that involves Isg15-activating E1 enzyme (UBE1L), Isg15-conjugating E2 enzyme (UBCH8), and Isg15 E3 ligase with HERC5 being the main E3 ligase for Isg15 [6-10]. …”
Section: Introductionmentioning
confidence: 99%